Global burden and unmet needs in the treatment of transfusion-dependent β-thalassemia - Forni, Gian Luca; Grazzini, Giuliano; Boudreaux, Jeanne; Agostini, Vanessa; Omert, Laurel (Frontiers in Hematology, 2023)
β-thalassemia is part of a group of inherited hemoglobinopathies caused by a mutation in the beta-globin gene, leading to minimal functional hemoglobin and resulting in damaged red blood cells and anemia. β-thalassemia is most common in the Mediterranean region, South-East Asia, the Indian subcontinent, and the Middle East. Many of these regions include low- and middle-income countries where there are significant unmet needs for adequate care and management of thalassemia. Patients with transfusion-dependent β-thalassemia, the most severe form of the disease, require regular blood transfusion. Chronic transfusions are often accompanied by iron chelation therapy to manage ferritin levels. Complications caused by transfusion and iron overload are only partially addressed by current treatment strategies, which negatively affects quality of life of patients with transfusion-dependent β-thalassemia. Until curative modalities become available for all patients worldwide, methods of optimizing supportive treatments are needed to reduce the symptoms of ineffective erythropoiesis and the impact on physical and mental wellbeing, minimize transfusion-related reactions and side effects, alloimmunization and transfusion-transmitted infections, and reduce the psychosocial burden on both the patient and their caregivers. This review aims to provide an overview and comparison of the ways transfusion-dependent β-thalassemia is identified and treated in different geographic regions, to assess unmet needs specific to these regions, and to discuss how therapies currently in development may improve care.